Idea of Peace in the Speeches of Pope John Paul II at the United Nations Forum from 1979–1995 and the Messages for the World Day of Peace from 1979–1991 - Owczarek, Michał (Vade Nobiscum, tom XX/2019: Studia z historii politycznej i wojskowej, 2019)
The Cold War was a time of very tense international relations. It will be interesting to answer the question: how did the Holy Father understand the world peace? How did he see a global situation? Was cold war present in the Holy Father messages? What should people do for the world peace? That problem was very important for the Catholic Social Teaching. Holy Father spoke of the world peace in many of his messages. John Paul II saw many aspects of that problem in his teaching. The initiative of Paul VI, who invented the World Day of Peace, during which the Pope gave a specially prepared message, became very important. This work was continued by John Paul II and is cultivated to the present day. The Polish pope took the understanding of peace from Paul VI, saying that it is synonymous with development. In addition, the papal perception was distinguished by holism. In his speeches, the Pope clearly recognized that during the Cold War, the issue of world peace was permanently under threat. This fact was influenced by the divisions of the world into blocks, among which he distinguished: East–West and North–South. As the main conception to master the world order, John Paul II saw dialogue. The dialogue was inseparably connected with another concept, which was a papal recipe for the deadly threat of nuclear war – negotiations. Unfortunately, apart from expressing broad approval for the words and actions of the Pope or the Holy See, no further actions of the states followed.